Marmota camtschatica - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Marmota camtschatica (Pallas, 1811). Zoogr. Rosso-Asiat., p. 156. TYPE LOCALITY: U.S. S. R., R.S.F.S. R., Kamchatsk. Obi. DISTRIBUTION: E. Siberia from Transbaikalia to Chukotka and Kamchatka (U.S. S. R.). COMMENT: Hoffmann et al., 1979, Occas. Pap. Mus. Nat. Hist. Univ. Kans., 83:1 -56, reviewed this species. Regarded by Ellerman and Morrison-Scott, 1951, and Rausch, 1953, Arctic, 6:91-148, as a synonym of marmota. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 1), pp. 345-382 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 355, DOI: 10.5281/zenodo.7353023